PENGARUH RESTRUKTURISASI KOGNITIF TERHADAP STRES AKADEMIK SISWA MELALUI BIMBINGAN KELOMPOK DI SMA NEGERI 8 PEKANBARU - Rahma Pertiwi; Rosmawati Rosmawati; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the differences in students 'academic stress levels before and after cognitive restructuring techniques were given through group guidance and find out the effect of cognitive restructuring techniques through group guidance to reduce students' academic stress levels. This research was conducted in SMA Negeri 8 Pekanbaru towards 7 subjects with purposive sampling technique. The research design was pre-experiment with the one group pre-test post-test model. The instrument of data collection used was an academic stress level questionnaire. The results showed that there were differences in the ways of thinking and behavior of students before and after the cognitive restructuring technique was given with a significance value of 0.018 <0.05. The effect of cognitive restructuring therapy on student stress levels is 64% while the other 36% is influenced by factors that come from within and from the student's environment.Key Words: Cognitive Restructuring, Academic Stress, Group Guidance